Augmented Reality as Potential Alternative Media for Paperless Advertising - Pratikta Aditya Setiawan (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
Today we life in the era of technology and information. Technology has become an important tools in human daily need and being used in every field of works, including advertisement. With the rapid development of technology, information can be accessed easily in faster speed and in higher quantity. In advertising, information is one of the most important element, we want our advertisement to contain information about our products and delivered in a fastest pace as possible with enough attraction element in it, also we want our advertisement to reach as many people as possible. Ironically, in the era of technology, we still using papers in our advertisement like posters, brochures, booklets, and many other printed promotional tools. The high demand for papers gives negative impact for nature, not only for the trees and forest, but also for the ecosystem. The rapid development of technology has given us so many new alternatives media in advertising, one of them is augmented reality. Augmented reality have a lot of potential to use in many fields of works including advertising. This study attempts to give comparisons between conventional media and Augmented Reality in advertising. The interesting thing of this study is to learn the weakness and the strength of paper media and Augmented Reality in advertising, and to learn how technology can be used indirectly for preserving nature.